2016
DOI: 10.1136/bmjopen-2015-008545
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nesiritide in patients with decompensated heart failure: a meta-analysis of randomised trials

Abstract: ObjectivesCurrent evidence suggests that nesiritide may have effects on renal function and decrease the incidence of mortality. However, a clear superiority using nesiritide in terms of renal toxicity and mortality in patients with heart failure was not consistently proven by previous studies. We performed a meta-analysis of all randomised trials to obtain the best estimates of efficacy and safety of nesiritide for the initial treatment of decompensated heart failure.MethodWe performed a meta-analysis of rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
2
14
1
Order By: Relevance
“…Recently, Gong et al 15 published the results of a meta‐analysis of randomized trials that investigated nesiritide use in patients with decompensated HF (n = 38 064 patients, in 22 trials). They revealed that nesiritide was not associated with a risk of mortality in patients with HF.…”
Section: Clinical Effectiveness Of Activating Specific Natriuretic Pecontrasting
confidence: 61%
See 1 more Smart Citation
“…Recently, Gong et al 15 published the results of a meta‐analysis of randomized trials that investigated nesiritide use in patients with decompensated HF (n = 38 064 patients, in 22 trials). They revealed that nesiritide was not associated with a risk of mortality in patients with HF.…”
Section: Clinical Effectiveness Of Activating Specific Natriuretic Pecontrasting
confidence: 61%
“…Even symptomatic improvements were only mildly demonstrated. Other, much smaller trials assessing infusions of NPs have been more positive, however 15,108 . Whether this can be explained by discrepancies in patient populations, doses or durations of treatment, only further studies will reveal.…”
Section: Limitations Of the Current Evidence Basementioning
confidence: 99%
“…In patients with low out-put syndrome, inotropic(s) and/or inodilator, such as levosimendan, are used to tory heart failure that showed nesiritide was associated with improved urine output, serum creatinine, and cardiac function [8,9]. However, trials in adults with acute decompensated heart failure have failed to show that nesiritide is associated with lower mortality or rehospitalization rate, or that it improves dyspnea.…”
Section: Inotropes and Inodilatorsmentioning
confidence: 99%
“… 29 ) Meta-analyses of clinical experience with nesiritide performed in 2005 and again in 2016 identified either a significantly increased risk of worsening renal function 30 or no obvious renal-protective benefit and some cardiovascular hazards (hypotension, bradycardia). 31 …”
Section: Acute Crs With Normal or High Blood Pressurementioning
confidence: 99%